(untitled) (Global Journal of Human-Social Science, 2014)
The aim of this paper is to analyze stereotype construction of gender roles in the text of children’s stories which inculcate in the children’s crude minds socially developed gender differences. For this purpose study followed Dell Hymes speaking model. This model has sixteen components that can be applied to different types of Discourse (speech interaction): message form; message content; setting; scene; Speaker/sender; address or; the hearer/receiver/ audience; addressee; purposes (outcomes); purposes (goals); key; channels; forms of speech; norms of interaction; norms of interpretation; and genres. Selected children’s stories were analyzed to identify their role as primary thought developing sources in the mind of young learners thus shaping their gender identities. This study would be beneficial in drawing the attention of authors, editors and writers of children’s literature to redefine gender roles in order to minimize gender differences.